MATHEMATICAL AND COMPUTER MODELING OF ECOLOGICAL AND ECONOMIC STATE FOR A REGION: PROBLEMS OF IDENTIFICATION, FORECASTING, ATTAINABILITY AND CONTROL - Chadov, A.L. (Perm Federal Research Centre Journal, 2014)
The main results obtained during the project № 10-01-96054 “Mathematical and computer modeling of ecological and economic state for a region: problems of identification, forecasting, attainability and control” are described in this paper in a popular form. The aim of the project was to develop mathematical and software bases for construction of mathematical models complex of ecological and economic state of the region taking into account the specifications, diversity and relationship processes occurring in the region. The created complex is focused on studying the stability of dynamic models, forecasting ecological and economic state of the region and solving control problems with finding the control variables and corresponding trajectory of development.